To find the linear function that has the same structure as the arithmetic sequence \( a_n = 6 + (n - 1) \cdot 8 \), we can start by rewriting the arithmetic sequence equation in a more recognizable form.
The equation \( a_n = 6 + (n - 1) \cdot 8 \) can be simplified as follows:
- Distribute the 8: \[ a_n = 6 + 8n - 8 \]
- Combine like terms: \[ a_n = 8n - 2 \]
Now, this equation \( a_n = 8n - 2 \) has a structure similar to a linear function \( y = mx + b \) where:
- \( m = 8 \) (the coefficient of \( n \))
- \( b = -2 \) (the constant term)
Thus, the linear function that matches the arithmetic sequence is:
\[ y = 8x - 2 \]
Therefore, the correct response is:
y = 8x - 2.